Profiles of met and unmet care needs in the oldest old primary care patients with cognitive disorders and dementia: results of the AgeCoDe and AgeQualiDe study - Kraake, Sophia; Pabst, Alexander; Bickel, Horst; Pentzek, Michael; Fuchs, Angela; Wiese, Birgitt; Oey, Anke; König, Hans-Helmut; Brettschneider, Christian; Scherer, Martin; Mallon, Tina; Lühmann, Dagmar; et al. (Dementia and geriatric cognitive disorders, 2024)
Introduction: The prevalence of mild cognitive impairment (MCI) and dementia is increasing as the oldest old population grows, requiring a nuanced understanding of their care needs. Few studies have examined need profiles of oldest old patients with MCI or dementia. Therefore, this study aimed to identify patients’ need profiles. Methods: The data analysis included cross-sectional baseline data from N = 716 primary care patients without cognitive impairment (n = 575), with MCI (n = 97), and with dementia (n = 44) aged 85+ years from the multicenter cohort AgeQualiDe study “needs, health service use, costs and health-related quality of life in a large sample of oldest old primary care patients [85+]”. Patients’ needs were assessed using the Camberwell Assessment of Needs for the Elderly (CANE), and latent class analysis identified need profiles. Multinomial logistic regression analyzed the association of MCI and dementia with need profiles, adjusting for sociodemographic factors, social network (Lubben Social Network Scale [LSNS-6]), and frailty (Canadian Study of Health and Aging-Clinical Frailty Scale [CSHA-CFS]). Results: Results indicated three profiles: “no needs,” “met physical and environmental needs,” and “unmet physical and environmental needs.” MCI was associated with the met and unmet physical and environmental needs profiles; dementia was associated with the unmet physical and environmental needs profile. Patients without MCI or dementia had larger social networks (LSNS-6). Frailty was associated with dementia. Conclusions: Integrated care should address the needs of the oldest old and support social networks for people with MCI or dementia. Assessing frailty can help clinicians to identify the most vulnerable patients and develop beneficial interventions for cognitive disorders.
Gesehen am 24.03.2025